Starting open source collaborative innovation: the antecedents of network formation in community source. (22nd July 2016) - Liu, Manlu; Hull, Clyde Eiríkur; Hung, Yu‐Ting Caisy
Abstract: Specific needs in the area of enterprise applications have led to a new type of collaborative open source innovation development across institution borders: community source. We use the Kuali community source network, a jointly managed, border‐spanning organization that supplies the institutions that created it, to describe how community source works. This study builds a theoretical basis for understanding the individual and institutional factors affecting community source network formation and the decision by organizations to join a community source network. We identify eight antecedents of decisions about forming or joining community source initiatives: motives, learning, trust, norms and monitoring, institutional similarity, external funding, hostile external environment and information technology. © 2016 John Wiley & Sons Ltd